The tale of the mandarin ducks - Paterson, Katherine (Lodestar Books, 1990)
A pair of mandarin ducks, separated by a cruel lord who wishes to possess the drake for his colorful beauty, reward a compassionate couple who risk their lives to reunite the ducks.